Diversity of Plants and Their Cultural Significance in The Kotagede Heritage Sites, Yogyakarta, Indonesia - Eka Sulistiyowati; Rizzana Tsuroyyaa Wira Perdana (Jurnal Biologi Tropis, 2023)
This research aims to demonstrate the value of intangible assets at heritage sites for species conservation. The study is located in Kotagede, a remnant of the Kingdom of Mataram Islam. A floristic survey was performed at major sites, including the Grand Mosque, the Royal Cemeteries, and the Water Reservoir Area (Sendang). Data on intangible knowledge of plants was collected through interviews with caretakers (juru kunci) and visitors to Kotagede. A total of 61 species from 41 families of angiosperms were recorded, and many of them were cultivated and purposefully planted for cultural needs. Several species were cultivated due to their medicinal use and source of food. Overall, this study concluded that heritage sites serve as physical assets for preserving history and intangible assets that contain intangible value. Conservation of plant species occurs due to cultural and philosophical values that are closely related to the existence of the heritage.